Cancer stem cells are prevalent in the basal-like 2 and mesenchymal triple-negative breast cancer subtypes in vitro - Olsson, Maxim; Larsson, Peter; Johansson, Junko; Sah, Vasu R.; Parris, Toshima Z. (Frontiers in Cell and Developmental Biology, 2023)
Background: Triple-negative breast cancer (TNBC) is an aggressive subtype with the most unfavorable clinical outcomes, in part due to tumor heterogeneity, treatment resistance, and tumor relapse. The TNBC subtypes (basal-like 1 [BL1], basal-like 2 [BL2], mesenchymal [M], and luminal androgen receptor [LAR]) are biologically and clinically distinct entities that respond differently to local and systemic therapies. Therefore, we need to have a better understanding of cancer stemness relating to drug-resistant populations in the TNBC subtypes. Methods: Breast cancer stem cell (BCSC) distribution was investigated using an integrated flow cytometry approach with the ALDEFLUOR™ assay (ALDH) and CD24/CD44 antibodies. In total, 27 commercially available cell lines derived from normal and malignant mammary tissue were characterized into differentiated tumor cells and/or BCSC subpopulations (ALDH-CD44+CD24-/low enriched mesenchymal-like BCSCs, ALDH+non-CD44+CD24−/low enriched epithelial-like BCSCs, and highly purified ALDH+CD44+CD24−/low BCSCs). Results: BCSCs were not only enriched in estrogen receptor (ER) negative (mean, 49.6% versus 6.9% in ER+) and TNBC cell lines (51.3% versus 2.1% in Luminal A), but certain BCSC subpopulations (e.g., enriched mesenchymal-like BCSCs) were also significantly more common in the M (64.0% versus 6.2% in BL1; 64.0% versus 0% in LAR) and BL2 (77.4% versus 6.2% in BL1; 77.4% versus 0% in LAR; 77.4% versus 10.4% in TNBC UNS) TNBC subtypes. In contrast, ALDH status alone was not indicative of ER status or BC subtype. Conclusions: Taken together, these findings demonstrate the enrichment of potentially treatment-resistant BCSC subpopulations in the M and BL2 triple-negative breast cancer subtypes.